TO THE 90TH ANNIVERSARY OF BIRTHDAY OF PROFESSOR V.G. BELIKOV - B. V. Borovsky; M. V. Larsky; O. O. Frolova (Фармация и фармакология (Пятигорск))
The article is devoted to basic life milestones of Professor, Doctor of Pharmaceutical Science, Honored Scientist of Russia V.G. Belikov, who made a great contribution to the development of domestic pharmaceutical education and science, more than 30 years headed the leading pharmaceutical institution of the country.